Machine-apparatus chart for the production of beta-glucan from spent brewer's yeast - Omelianenko, Kostiantyn; Avramia, Ionut; Kasyniuk, Maksym; Hrininh-Hera, Kateryna (My University, 2024)
An important step in extracting beta-glucan is the destruction of yeast cells. The description of the machine-apparatus chart for this production of beta-glucan from the walls of used brewer's yeast is not available in the scientific and technical literature. The process of industrial destruction of used brewer's yeast needs research. The developed chart can be used in the educational process of engineering of food, pharmaceutical and biotechnological industries.
Keywords: бета-глюкан; beta-glucan; пивні дріжджі; brewer's yeast; кафедра мехатроніки та пакувальної техніки